Can red blood cell distribution width (RDW) level predict the severity of acute exacerbation of chronic obstructive pulmonary disease (AECOPD)?. Issue 11 (19th August 2021) - Alparslan Bekir, Sumeyye; Tuncay, Eylem; Gungor, Sinem; Yalcinsoy, Murat; Sogukpinar, Özlem; Gundogus, Baran; Aksoy, Emine; Agca, Meltem; Agca Altunbey, Sinem; Turker, Hatice; Karakurt, Zuhal
Abstract: Background: Elevated red blood cell distribution width (RDW) levels were associated with mortality in patients with stable chronic obstructive lung pulmonary diseases (COPD). There are limited data about RDW levels in acute exacerbation of COPD (AECOPD). Aim/Objective: The association of the RDW levels with the severity of AECOPD was evaluated according to admission location, (outpatient‐clinic, ward and intensive care unit (ICU)). Methods: Cross sectional retrospective study was designed in tertiary care hospital for chest diseases in 2015. Previously COPD diagnosed patients admitted to hospital outpatient‐clinic, ward and ICU due to AECOPD were included in the study. Patients demographics, RDW, biomarkers (CRP, RDW, Neutrophil to lymphocyte ratio (NLR), platelet to mean platelet volume (PLT‐MPV)) C‐CRP, biochemistry values were recorded from hospital electronic system. RDW values were subdivided below 0.11% (low), above and equal 0.15% (high) and between 0.11%‐0.15% (normal). Neutrophil to lymphocyte ratio (NLR) and platelet to mean platelet volume (PLT‐MPV) were also calculated. Biomarker values were compared according to where AECOPD was treated. Results: 2771 COPD patients (33% female) and 1429 outpatients‐clinic, 1156 ward and 186 ICU were enrolled in the study. The median RDW values in outpatients‐clinic, ward and ICU were 0.16 (0.09‐0.26), 0.07 (0.01‐0.14) and 0.01 (0.00‐0.07) respectively (P < .001). In outpatient to ward and ICU, low RDW values were significantly increased (31%, 66%, 83%, respectively) and high RDW values significantly decreased (54%, 24%, 10%) (P < .001). According to attack severity, low RDW values were determined. Conclusion: Patients with AECOPD, lower RDW values should be considered carefully. Lower RDW can be used for decision of COPD exacerbation severity and follow up treatment response